Secrets of Ancient Cultures The Inca : activities and crafts from a mysterious land - Braman, Arlette N., 1952-; Nidenoff, Michele (Hoboken, N.J. : Wiley, 2004)
Provides information on the civilization of the ancient Incas and directions for activities and crafts based on their culture.
Keywords: Indian craft -- Juvenile literature; Incas -- Material culture -- Juvenile literature; Handicraft; Incas; Indians of South America; Indian craft